Modern weapons and military equipment for issue 2-2017 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Russia's Sukhoi Super 30: The Outlook for India’s Ultra-Advanced Flanker Upgrade; In harm’s way.